Postsecondary Students’ Information Needs and Pathways for Help with Stress, Anxiety, and Depression - Stewart, Donald W.; Walker, John R.; Beatie, Brooke; Reynolds, Kristin A.; Hahlweg, Ken; Leonhart, Mark; Tulloch, Alexandria; Research Group, The Mobilizing Minds (Canadian Journal of Counselling and Psychotherapy, 2014)
Surveys indicate that prevalence rates of depression, anxiety, and other disorders in postsecondary students are equal to or higher than those in the general population; however, students often do not access help for these problems. Moreover, those who do seek help are confronted by a range of choices involving psychological, pharmacological, or combined treatment, along with multiple sources of information regarding treatment options. In an effort to identify the information needs and preferences of Canadian university students, we conducted a survey of students seeking counselling or medical services on campus. Results indicated that students were more likely to initially seek advice from romantic partners or friends rather than counsellors or health care providers. When asked to consider what information is important when seeking help, students reported that treatment effectiveness, advantages/disadvantages of treatment, side effects, and what happens when treatment is stopped were all very important. Training and experience of service providers were seen as more important than providers’ recommendations for type of treatment. Meetings with a counsellor were preferred over medication as a treatment modality. Preferred sources of information included health care providers, information sheets, and the Internet. Implications of the survey for postsecondary mental health service delivery are discussed. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>